Effects of Bone Marrow Mesenchymal Stromal Cell Therapy in Experimental Cutaneous Leishmaniasis in BALB/c Mice Induced by Leishmania amazonensis - Pereira, Joyce Carvalho; Ramos, Tadeu Diniz; Silva, Johnatas Dutra; de Mello, Mirian França; Pratti, Juliana Elena Silveira; da Fonseca-Martins, Alessandra Marcia; Firmino-Cruz, Luan; Kitoko, Jamil Zola; Chaves, Suzana Passos; Gomes, Daniel Claudio De Oliveira; Diaz, Bruno Lourenço; Rocco, Patricia R. M.; et al. (Frontiers in Immunology, 2017)
Cutaneous leishmaniasis remains both a public health and a therapeutic challenge. To date, no ideal therapy for cutaneous leishmaniasis has been identified, and no universally accepted therapeutic regimen and approved vaccines are available. Due to the mesenchymal stromal cell (MSC) immunomodulatory capacity, they have been applied in a wide variety of disorders, including infectious, inflammatory and allergic diseases. We evaluated the potential effects of bone marrow MSC therapy in a murine model of cutaneous leishmaniasis. In vitro, co-culture of infected macrophages with MSC increased parasite load on macrophages in comparison with controls (macrophages without MSCs). In vivo, BALB/c mice were infected with 2x106 Leishmania amazonensis (Josefa strain) promastigotes in the footpad. Seven days and thirty-seven days after infection, animals were treated with 1x105 MSCs, either intralesional (i.l.), i.e., in the same site of infection, or intravenously (i.v.), through the external jugular vein. Control animals received the same volume (50 μl) of PBS by i.l. or i.v routes. The lesion progression was assessed by its thickness measured by pachymetry. Forty-two days after infection, animals were euthanized and parasite burden in the footpad and in the draining lymph nodes was quantified by the limiting dilution technique (LDA), and spleen cells were phenotyped by flow cytometry. No significant difference was observed in lesion progression, regardless of the MSC route of administration. However, animals treated with i.v. MSCs presented a significant increase in parasite load in comparison with controls. On the other hand, no harmful effect due to MSCs i.l administered was observed. The spleen cellular profile analysis showed an increase of IL-10 producing T CD4+ and TCD8+ cells in the spleen only in mice treated with i.v. MSC. The excessive production of IL-10 could be associated with the disease-aggravating effects of MSC therapy when intravenously administered. As a conclusion, in the current murine model of Leishmania amazonensis induced cutaneous disease, MSCs did not control the damage of cutaneous disease and, depending on the administration route, it could result in deleterious effects.